2015
DOI: 10.1007/s11064-015-1568-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Pioglitazone in the Hippocampal CA1 Region Following Transient Forebrain Ischemia in Low- and High-Fat Diet-Fed Gerbils

Abstract: In the present study, we investigated the effects of pioglitazone (PGZ) in the hippocampal CA1 region of low- or high-fat diet (LFD or HFD) fed gerbils after transient forebrain ischemia. After 8 weeks of LFD or HFD feeding, PGZ (30 mg/kg) was intraperitoneally administered to the gerbils, following which ischemia was induced by occlusion of the bilateral common carotid arteries for 5 min. Administration of PGZ significantly reduced the ischemia-induced hyperactivity 1 day after ischemia/reperfusion in both LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…To elucidate the effects of pyridoxine deficiency on lipid peroxidation induced by ischemia, transient forebrain ischemia was induced with occlusion of common carotid arteries, and the animals ( n = 5 per group) were sacrificed at 3, 12, and 24 h after ischemia/reperfusion on the 56th day of diet feeding. Both hippocampi were quickly removed, and MDA levels were measured with a Bioxytech MDA-586 kit (Oxis Research, Portland, OR, USA) as described in the previous study [ 59 ]. MDA levels were normalized to the protein concentration and the assay was triplicated.…”
Section: Methodsmentioning
confidence: 99%
“…To elucidate the effects of pyridoxine deficiency on lipid peroxidation induced by ischemia, transient forebrain ischemia was induced with occlusion of common carotid arteries, and the animals ( n = 5 per group) were sacrificed at 3, 12, and 24 h after ischemia/reperfusion on the 56th day of diet feeding. Both hippocampi were quickly removed, and MDA levels were measured with a Bioxytech MDA-586 kit (Oxis Research, Portland, OR, USA) as described in the previous study [ 59 ]. MDA levels were normalized to the protein concentration and the assay was triplicated.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that the level of blood glucose, triglyceride, total cholesterol, and low-density lipoprotein cholesterol levels were significantly increased in this gerbil model of HFD [ 1 ]. In addition, it has been reported that, in gerbils fed HFD for 8 weeks, body weight, level of blood glucose, triglyceride and total cholesterol are significantly increased compared with gerbils fed ND [ 35 ]. The negative effect of obesity in gerbils was observed after 4–6 months of HFD feeding [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of obesity in gerbils was observed after 4–6 months of HFD feeding [ 36 ]. Above-mentioned authors have reported that ischemia-reperfusion injury exacerbates neuronal damage in the striatum [ 1 ] and septum [ 35 ] of gerbils fed HFD. In the case of rats, HFD feeding for 3 months worsens the outcome of neuronal damage after endothelin-induced ischemia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a condition characterized by an excessive accumulation of body fat that can lead to metabolic abnormalities, such as hyperlipidemia, hypercholesterolemia, and hyperglycemia, all of which can affect the pathophysiology of ischemic insults [33,34]. In this study, we set up a HFD-induced obese gerbil model to investigate effects of a 2-min TI on the neuronal damage in the hippocampus of HFD-induced obese gerbils.…”
Section: Discussionmentioning
confidence: 99%